A 350-GHz SIS antipodal finline mixer - Yassin, G; Withington, S; Buffey, M; Jacobs, K; Wulff, S (2000)
In this paper, we describe the design and operation of a 350-GHz flnline superconductor-insulator-4superconductor mixer. The mixer is fed by a horn-reflector antenna, and the superconducting circuit is fabricated using planar-circuit technology and fully integrated tuning. An important feature of the mixer is that it employs an antipodal flnline section, deposited on one side of a quartz substrate, which transforms the high impedance of the waveguide (~300 fi) to the low impedance of the microstrip (-420 II). The Nb/Al-oxide/Nb tunnel junction is fabricated at the same time as the flnline circuit. In this paper, we describe the design procedure in some detail. We pay particular attention to the synthesis of the flnline taper and the electromagnetic design of the horn-reflector antenna. We have tested a flnline mixer over the frequency range of 330-370 GHz and measured a receiver noise temperature of 90 K, which remained unchanged over the whole frequency range. Our investigation has demonstrated that it is possible to make superconducting flnline mixers for frequencies as high as 350 GHz. © 2000 IEEE.